RMG Industry in Bangladesh: In search of Strategies for Creating and Sustaining Competitive Advantages Using Business Model Canvas - Jahan, Sheikh Morshed; Rahman, Gazi Mueedur; Islam, Rummanun (International Journal of Scientific Research and Management (IJSRM), 2018)
Ready-made Garments (RMG) industry is one of the major drivers of the economy of Bangladesh as it accounts for more than 80% of the national export revenue of Bangladesh and employs about 5 million people, mostly women. This sector is becoming more exposed to the competition in global market, while it is haunted by tragedies such as Rana Plaza fire incidence. Most of the firms in this industry used to adopt cost-leadership strategy at the expense of good workplace practices and compliance. This approach no longer works because of the increased monitoring of international activists, suppliers, buyers, and the government of Bangladesh. To overcome this challenge, firms need to develop new strategies by redesigning their business model. Given the major competitive challenges that the industry is facing today, this study identifies some strategic imperatives for the firms to keep pace with the changing local and global dynamics involving the RMG industry